2020
DOI: 10.1007/s11357-020-00187-z
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial adaptations in liver and skeletal muscle to pro-longevity nutritional and genetic interventions: the crosstalk between calorie restriction and CYB5R3 overexpression in transgenic mice

Abstract: Calorie restriction without malnutrition (CR) is considered as the most effective nongenetic nor pharmacological intervention that promotes healthy aging phenotypes and can extend lifespan in most model organisms. Lifelong CR leads to an increase of cytochrome b 5 reductase-3 (CYB5R3) expression and activity. Overexpression of CYB5R3 confers some of the salutary effects of CR, although the mechanisms involved might be independent because key aspects of energy metabolism and lipid profiles of tissues go in oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
5
8
0
Order By: Relevance
“…A previous in vivo study using male C57BL/6 mice fed a CR diet (40% restriction) for 6 months revealed increased levels of MFN2 and OPA1 in skeletal muscle ( 107 ). A similar finding has also found in mice fed a CR diet (40% restriction) with less calories, that expressed increased levels of MFN1 and NRF1 ( 110 ). Additionally, the prolonged duration of CR was found to have no effect on mitochondrial fusion, proposing that initial energy deprivation led to a rather early control of mitochondrial fusion ( 107 ).…”
Section: Dietssupporting
confidence: 81%
See 1 more Smart Citation
“…A previous in vivo study using male C57BL/6 mice fed a CR diet (40% restriction) for 6 months revealed increased levels of MFN2 and OPA1 in skeletal muscle ( 107 ). A similar finding has also found in mice fed a CR diet (40% restriction) with less calories, that expressed increased levels of MFN1 and NRF1 ( 110 ). Additionally, the prolonged duration of CR was found to have no effect on mitochondrial fusion, proposing that initial energy deprivation led to a rather early control of mitochondrial fusion ( 107 ).…”
Section: Dietssupporting
confidence: 81%
“…On the contrary, the study showcased an elevation at DRP1 levels in mitochondria-enriched fractions of hepatocytes ( 113 ), indicating that a similar CR diet is able to affect mitochondrial dynamics differently between tissues. Another study revealed that the CR diet was not able to change the mitochondrial abundance in hepatocytes, but stimulated MFN2 levels ( 110 ).…”
Section: Dietsmentioning
confidence: 99%
“…1C, Table S1). The proteins whose concentrations increased with cell size included CDC27, a component of the anaphase-promoting complex, and CYB5R3, an antioxidant enzyme linked to longevity (17). The median relative concentration change for the 3171 proteins was -0.18; 95%CI = [-0.20, -0.17], indicating that most proteins are progressively diluted with increasing cell size.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are closely involved in liver metabolism. Though several studies have revealed multiple mitochondrial adaptions during different forms of CR, [ 35 , 36 , 37 ] how liver mitochondria responding to specific ADF intervention has not been investigated. The metabolomics analysis of mouse liver after ADF led us to propose certain metabolic remodeling may occur in mitochondria, since most altered metabolites were primarily associated with amino acid metabolism (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%